1999
DOI: 10.1093/ije/28.5.925
|View full text |Cite
|
Sign up to set email alerts
|

Can accurate data on birthweight be obtained from health interview surveys?

Abstract: ResultsThe estimates suggest that a substantial proportion of women whose newborns were probably never weighed report a birthweight. For all of the surveys, with the possible exception of Costa Rica, the average birthweights appear to be too high, and the estimates of the prevalence of low birthweight too low. In addition, the data reveal anomalous patterns, such as higher birthweights for home as compared with hospital deliveries.Conclusions These findings suggest that estimates of low birthweight derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
(11 reference statements)
0
16
0
1
Order By: Relevance
“…Another concern is that previous research has shown that there may be errors in the reporting of birth-weight data in surveys (Boerma et al 1996; Robles and Goldman 1999). We estimated alternative models with birth weight divided into three categories: low, average, and high.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern is that previous research has shown that there may be errors in the reporting of birth-weight data in surveys (Boerma et al 1996; Robles and Goldman 1999). We estimated alternative models with birth weight divided into three categories: low, average, and high.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case in 6638 of 31 148 children included in the NNS. An indication of good data quality is the low degree of heaping observed: only 19% of the birthweights are multiples of 500 g. This is considerably lower than that observed in birthweight data from other population surveys (Robles and Goldman 1999).…”
Section: Data Descriptionmentioning
confidence: 72%
“…Another probable reason for the discrepancy is errors in the measurement for those infants who were actually weighed. Both these lapses are common in less developed countries (Boerma et al 1996;Robles and Goldman 1999;Blanc and Wardlaw 2005).…”
Section: Sample Characteristicsmentioning
confidence: 99%